2022
DOI: 10.1186/s12879-022-07194-9
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care urine Gram stain led to narrower-spectrum antimicrobial selection for febrile urinary tract infection in adolescents and adults

Abstract: Background Febrile urinary tract infections (fUTIs), which include pyelonephritis, prostatitis, and urosepsis, are the most common cause of sepsis. However, the treatment has become more complex because of the worldwide increase in antimicrobial resistance (AMR). The objective of this study was to clarify whether point-of-care Gram stain (PCGS) of urine contributed to fUTI diagnosis and treatment in adults. Methods This hospital-based observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…After Okinawa was returned to Japan in 1972, the program continued, and Gram staining has remained an important procedure in the clinical practice of infectious diseases performed by physicians at Okinawa Chubu Hospital. In fact, many studies on the usefulness of Gram staining have been reported by physicians at this hospital 16–20 . Furthermore, postgraduate mandatory clinical residency training that began in Japan in 2004 has spread this concept to medical institutions other than Okinawa Chubu Hospital.…”
Section: History Of Gram Staining In Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…After Okinawa was returned to Japan in 1972, the program continued, and Gram staining has remained an important procedure in the clinical practice of infectious diseases performed by physicians at Okinawa Chubu Hospital. In fact, many studies on the usefulness of Gram staining have been reported by physicians at this hospital 16–20 . Furthermore, postgraduate mandatory clinical residency training that began in Japan in 2004 has spread this concept to medical institutions other than Okinawa Chubu Hospital.…”
Section: History Of Gram Staining In Clinical Practicementioning
confidence: 99%
“…In fact, many studies on the usefulness of Gram staining have been reported by physicians at this hospital. [16][17][18][19][20] Furthermore, postgraduate mandatory clinical residency training that began in Japan in 2004 has spread F I G U R E 1 Differences between Gram-stain guided antimicrobial therapy and general antimicrobial therapy. GNR, Gram-negative rods; GPB, Gram-positive bacilli; GPC, Gram-positive cocci.…”
Section: History Of Gr a M Sta I N I Ng I N Cl I N Ica L Pr Ac Ticementioning
confidence: 99%
See 1 more Smart Citation
“…As a form of point-of-care (POC) testing, urine Gram stains have been proven invaluable for the prompt diagnosis of urinary tract infection (UTI) [ 10 , 11 ]. POC Gram stain (PCGS) of urine showed a moderate correlation and high agreement with urine culture in both uncomplicated and complicated UTI [ 10 ].…”
mentioning
confidence: 99%
“…As a form of point-of-care (POC) testing, urine Gram stains have been proven invaluable for the prompt diagnosis of urinary tract infection (UTI) [ 10 , 11 ]. POC Gram stain (PCGS) of urine showed a moderate correlation and high agreement with urine culture in both uncomplicated and complicated UTI [ 10 ]. Despite limited data on clinical efficacy, previous studies have indicated that PCGS for both uncomplicated and complicated UTIs yields comparable treatment success rates to guideline-based therapy while also reducing the cost of broad-spectrum antimicrobials [ 12 ].…”
mentioning
confidence: 99%